Promoting HPV vaccination among Latinx: an application of the extended parallel processing model. - Reno, Jenna E.; Dempsey, Amanda F. (Journal of Behavioral Medicine, 2023)
Vaccine hesitancy is a substantial barrier to increasing HPV vaccination rates among Latinx in the US who experience disproportional rates of HPV-related cancers. The current research tests the effectiveness of culturally-targeted, fear-appeal messages designed using the Extended Parallel Processing Model (EPPM). We compared differences among Latinx young adults and parents of adolescents of the effectiveness of messages that highlight HPV-related cancers, genital warts, or a control condition to promote online information seeking about the HPV vaccine—a known precursor to vaccination intention. Results found messages containing EPPM messaging elements produced significantly higher self-reported intention to seek information about HPV vaccines in comparison to a control message group. However, participants who received control messages had the highest percentage of hyperlink clicks to more information about HPV (a novel measure of information seeking). Findings suggest that fear appeals may be effective for promoting information seeking about HPV vaccination, which in turn could increase vaccine utilization, among Latinx participants. Clinical trial registration number (NCT05206669) retrospectively registered January 25, 2022.